Association between serum total bilirubin and Alzheimer's disease: A bidirectional Mendelian randomization study. (November 2022) - Wang, Haiyan; Wu, Shuzhen; Wang, Lijuan; Gou, Xiaoyan; Guo, Xiaoling; Liu, Zhengping; Li, Pengsheng
Highlights: Previous studies have suggested that heme oxygenase and biliverdin reductase are involved in the development of Alzheimer's disease; however, the causal association between bilirubin and Alzheimer's disease is still controversial. In this two-sample Mendelian randomization study, the results do not support the causal association between bilirubin and Alzheimer's disease. Serum total bilirubin levels may not be suitable as biomarkers for early diagnosis or screening of Alzheimer's disease. Abstract: Oxidative stress plays an important role in the pathogenesis of Alzheimer's disease (AD). As a potent antioxidant, serum bilirubin is decreased in AD and may be related to its pathogenesis, but the causal association between serum bilirubin and AD has not been reported. This was investigated in the present study by bidirectional two-sample Mendelian randomization (MR) analysis. Genetic instruments at the genome-wide significance level ( P  < 5 × 10 −8 ) were selected from the United Kingdom Biobank ( n  = 342, 829). Summary-level AD data were obtained from a large-scale genome-wide association study ( n  = 63, 926). Causal estimates were evaluated using the inverse variance weighted (IVW) approach and other five complementary methods. MR-Egger, IVW and MR pleiotropy residual sum and outlier (MR-PRESSO) methods were used for sensitivity analyses. The results showed that there was no significant association between serum total bilirubin and AD (odds ratio=1.003, 95% confidence interval: 0.967–1.041, P  = 0.865). Inverse MR revealed that serum total bilirubin was increased in AD (beta = 0.009, SE = 0.003, P  = 0.010). These results indicate that serum total bilirubin is not causally associated with AD and cannot be used for screening or diagnosis, but can potentially serve as a biomarker of disease severity, and it needs further clinical studies.